PENGEMBANGAN DIRI (SPRITUAL KEAGAMAAN) MELALUI PENGAJIAN LANSIA DI MAJELIS TAKLIM SERUMPUN KABUPATEN ACEH BARAT - Martini; Fadhlur Rahman Armi (Prodi Pengembangan Masyarakat Islam STAIN Teungku Dirundeng Meulaboh, 2022)
This paper aims to determine the role of the Majelis Taklim in the context of guidance for elderly mothers in learning the Qur'an in the related Taklim Council. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. This research was conducted from March 10, 2021, to March 10, 2022. The subject of this research is any element or resource that exists in the Majelis Taklim of Serumpun. Data analysis techniques used are data reduction, data presentation, and drawing inferences. The results of this study show that; 1) The learning process at Serumpun Taklim Council is held once a week on Wednesday, every month on the third Wednesday there is learning about reading in the prayer for the dead, this meeting is held for 1-2 hrs classically and read, the method used is the Tsaqifa method and the material provided is the introduction of the Hijaiyah letter, how each Hijaiyah letter sounds and others.